THE DEVELOPMENT OF QUESTIONNAIRE TO INVESTIGATE STUDENTS ATTITUDES AND APPROACHES IN PHYSICS PROBLEM SOLVING (Jurnal Pendidikan Fisika Indonesia, 2017)
This study aims to develop physics problem solving survey utilized to obtain students’ attitude and approach while solving physics problem. Several steps are conducted to develop the survey: validating, computing reliability, and testing. This research involves Physics Education students-Tanjungpura University who study at Fourth and Sixth semester. Furthermore, after questionnaire administered to the students, data are analysed through determining average score of the students and computing average percentage of students who are agree, neutral, and disagree based on semester and gender. The results show that the sixth semester students’ responses are more expertlike than those of the fourth semester students and female students are less expert than those male students. Based on semester and gender, majority of students have the same attitudes and approaches while solving problems. Students and experts have different attitudes about the role of mathematics in problem solving.